Study on the thermal field material of FZ-Si crystal waste graphite purified by ultrasonic enhanced acid leaching - Yonghang Zhang; Zhengjie Chen; Keqiang Xie; Xiuhua Chen; Xiaowei Chen; Yiyou Hu; Wenhui Ma (Arabian Journal of Chemistry)
This study examines the acid-leaching and purification process of waste graphite in the production of Czochralski monocrystalline silicon. The optimal leaching conditions are identified as a liquid-to-solid ratio of 6, a leaching temperature of 70 °C, an acid concentration of 8 mol, and a leaching time of 60 min. The use of hydrofluoric acid, sulfuric acid, and nitric acid in the acid-leaching process increases the fixed carbon content of waste graphite from ∼94 % to ∼98.5 %. To address the low fixed carbon content that cannot be achieved through conventional acid-leaching, a method combining ultrasonic intensification with hydrofluoric and hydrochloric acid leaching is proposed and successfully implemented. Under ultrasonic enhancement conditions, the leaching effect is optimal at a temperature of 60 °C, acidity of 4 mol, and leaching time of 60 min. These results demonstrate that the introduction of ultrasound significantly strengthens the acid-leaching process. The method proposed in this study not only purifies waste graphite through acid-leaching but also elucidates the reaction behavior of various impurity elements during the leaching process. Overall, these findings provide a foundational basis for the recovery of waste graphite in the thermal field.